Improving Confidence in Obstetric Skills with Basic and Advanced Life Support in Obstetrics® Training in Ethiopia: A Pre/post Study - E. Evensen, Ann; M. Panzer, Jeffrey; S. Jones, Sarah; M. Wright, Katherine; Albelo, Adianez (Journal of Women's Reproductive Health, 2015)
Basic Life Support in Obstetrics (BLSO®) is a novel, simulation-based, emergency obstetrics training program for health care workers who perform deliveries infrequently, such as paramedics and nurses. Advanced Life Support in Obstetrics (ALSO®) is intended for regular maternity care providers such as physicians and certified nurse midwives. This paper describes a pre/post study of 111 learners in two ALSO and two BLSO courses taught in Addis Ababa, Bonga, and Jimma, Ethiopia in October, 2012. The study objective was to assess the effectiveness of ALSO and BLSO training programs to improve Ethiopian health care workers’ confidence in managing common obstetrical problems. A previously-validated survey tool was given immediately pre- and post-course and six months post-course. The survey tool included demographic questions and Likert scales to self-assess comfort managing 13 common obstetric emergencies including postpartum hemorrhage, maternal resuscitation, and preeclampsia. Ninety-seven ALSO and BLSO learners completed pre- and immediate post-training questionnaires. Nineteen ALSO learners completed the 6 month post-training questionnaire. Immediately post-course, participants in ALSO and BLSO courses reported increased comfort in all 13 areas assessed. ALSO participants had increased comfort at 6 months in all areas except breech delivery. Participation in a novel emergency obstetrics training program increases Ethiopian health workers’ self-assessed confidence in addressing common obstetrical emergencies. This increase in confidence persists in most topic areas for at least six months. This paper describes the first formal evaluation of BLSO and contributes to the growing body of evidence regarding the value of ALSO training in a low- and middle-income country.
Keywords: emergency obstetrics; team training; simulation training; maternal health; Ethiopia; global health